2015
DOI: 10.4102/phcfm.v7i1.810
|View full text |Cite
|
Sign up to set email alerts
|

Profile and correlates of functional status in elderly patients presenting at a primary care clinic in Nigeria

Abstract: BackgroundAssessing the functional status of elderly patients is central in measuring their health outcome. Little is known about the functional status of elderly patients attending our primary care clinic in Nigeria.ObjectiveTo assess the correlates of functional status in elderly patients presenting at the General Outpatient Clinic of the University College Hospital, Ibadan, Nigeria.MethodA cross-sectional study of 360 randomly selected patients aged 60 years and above was undertaken to assess their function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Functional assessment should be performed as part of a holistic treatment for the elderly. 15 All the life changes experienced by the elderly make them more sensitive, feeling of loneliness, depression, and isolation. Psychosocial aspects greatly affect one's physical health.…”
Section: Discussionmentioning
confidence: 99%
“…Functional assessment should be performed as part of a holistic treatment for the elderly. 15 All the life changes experienced by the elderly make them more sensitive, feeling of loneliness, depression, and isolation. Psychosocial aspects greatly affect one's physical health.…”
Section: Discussionmentioning
confidence: 99%
“…1 In a developing country like Nigeria, the same definition applies. 2 , 3 The population of older persons in Nigeria is reported to be increasing rapidly. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Their health profile is characterised by decreased immunity, multimorbidity, chronic illnesses, declining physical functions and impaired socialisation necessitating increased demand on healthcare services. 2 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…and South Africa(44) evaluated functional impairment in the elderly. Ajayi et al 2015 reported a prevalence of 83% of functional disability among participants above 60 years attending a primary care clinic inNigeria (35). The most prevalent functional disabilities were with grooming and personal hygiene, and transferring from bed to chair.…”
mentioning
confidence: 99%